Predictors of Sustained Response to Rivastigmine in Patients With Alzheimer's Disease: A Retrospective Analysis - Sadowsky, Carl H. (Physicians Postgraduate Press, Inc., 2011)
Objective: The cholinesterase inhibitor rivastigmine is approved for the treatment of mild to moderate Alzheimer's disease. However, it is not possible to predict which individuals will benefit from treatment. This retrospective analysis of an international, 24-week, randomized, double-blind trial aimed to identify the percentage of persons with Alzheimer's disease who have a sustained response with rivastigmine patch, rivastigmine capsules, or placebo; to determine the magnitude of the sustained treatment response; and to investigate baseline patient characteristics predictive of the observed sustained response. Method: Patients who improved on the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog) and Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL) at week 16 and maintained at least the week 16 improvement at week 24 were identified as sustained responders. Treatment differences and baseline predictive factors were assessed in patients demonstrating a 1-, 2-, 3-, 4-, or 5-point sustained improvement. The first patient was screened in November 2003 and the last patient completed the study in January 2006. Results: More persons with Alzheimer's disease had sustained improvements on the ADAS-cog and ADCS-ADL with rivastigmine versus placebo. Sustained improvements of 4 or 5 points on the ADAS-cog or ADCS-ADL were demonstrated in the 9.5-mg/24-h rivastigmine patch (24% and 36% of patients, respectively) and 12-mg/d capsule groups (28% on both outcome measures). Factors predictive of a sustained response to treatment included baseline Mini-Mental State Examination, ADAS-cog, and ADCS-ADL scores and treatment, country of treatment, and time since first symptom was diagnosed by a physician. Conclusions: Understanding factors predictive of sustained cholinesterase inhibitor treatment response should help to optimize Alzheimer's disease management and encourage compliance by allowing more realistic expectations of treatment effects.